'Off the shelf' immunotherapies: Generation and application of pluripotent stem cell‐derived immune cells. Issue 4 (1st March 2023) - Wang, Chenxin; Liu, Jingjing; Li, Wei
Abstract: In recent years, great strides have been made toward the development of immune cell‐based therapies in the treatment of refractory malignancies. Primary T cells and NK cells armed with chimeric antigen receptors have achieved tremendous clinical success especially in patients with leukaemia and lymphoma. However, the autologous origin of these effector cells means that a single batch of laboriously engineered cells treats only a certain patient, leading to high cost, ununiform product quality, and risk of delay in treatment, and therefore results in restricted accessibility of these therapies to the overwhelming majority of the patients. Addressing these tricky obstacles calls for the development of universal immune cell products that can be provided 'off the shelf' in a large amount. Pluripotent stem cells (PSCs), owing to their unique capacity of self‐renewal and the potential of multi‐lineage differentiation, offer an unlimited cell source to generate uniform and scalable engineered immune cells. This review discusses the major advances in the development of PSC‐derived immune cell differentiation approaches and their therapeutic potential in treating both hematologic malignancies and solid tumours. We also consider the potency of PSC‐derived immune cells as an alternative therapeutic strategy for other diseases, such as autoimmune diseases, fibrosis, infections, et al. Abstract : PSCs undergo unlimited self‐renewal and have the potential to differentiate into all cell types, which provides a reliable source of effective immune cells. These PSC‐derived immune cells elicit various immune responses and can be used to treat various diseases, such as leukaemia, solid tumours, autoimmune diseases, respiratory infections, fibrosis, et al.